Impact of Foreign Direct Investment In Retailing Sector: A Study on the Impact of Foreign Direct Investment in the Indian Retailing Sector (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India has growth prospect for retail industry with a hugenumber of consumers and other favorable factors. But India’s retail marketremains largely off-limits to large international retailers like Wal-Mart,Tesco and Carrefour. Opposition to liberalizing FDI in this sector raisesconcerns about employment losses, unfair competition resulting in large-scaleexit of incumbent domestic retailers and infant industry arguments to protectthe organized domestic retail sector that is at a nascent stage. In 2012 theIndian Government approved  proposal of100 percent  FDI  in   retailing  in  India subject  to certain conditions.Though this proposal  is being hailed byglobal  retail  giants, which until  now  have been  involved  in only wholesale  cash  and carry distribution  in  India and have been  longing for entry  into the  Indian retail market foryears.  The proposal has receivedvehement opposition from a spectrum of political parties in India, many of themurging for a reversal of the proposal. As a result,  the  Indian government has stalled  the implementation of  this proposalwhich has  temporarily washed off  the wishes of the  global retail  players  awaiting a  bite  of the  Indian  retail market. This paper attempts to studythe present status of FDI in retailing sector in India and the impacts of FDIon various concerned segments.